PENGARUH EFEKTIFITAS MANAJERIAL DAN EFIKASI DIRI TERHADAP MOTIVASI KERJA DOSEN KEBIDANAN POLTEKKES PROVINSI LAMPUNG - SUDARMI, SUDARMI (Jurnal Ilmiah Educational Management, 2015)
The objective of this research is to explore the effect of managerial effectiveness, self-efficacy, on the work motivation of midwifery lectures Poltekkes in Lampung Province. This research used a quantitative survey method with path analysis. The results of this research: the managerial effectiveness of a direct positive effect on work motivation, self-efficacy of a direct positive effect on work motivation, of and managerial effectiveness direct positive effect on self-efficacy.